Konstruktive Konzepte : Eine Geschichte der konstruktiven Kunst vom Kubismus bis heute - Rotzler, Willy (Zürich : ABC Verlag, 1977)
Adams, Robert ; Agam, Yaacov ; Albers, Josef ; Alfano, Carlo ; Alkema, Wobbe ; Annenkow, Jurii ; Anuszkiewicz, Richard ; Arakawa, Shusaku ; Arp, Hans ; Baertling, Olle ; Baljeu, Joost ; Balla, Giacomo ; Balth, Carel ; Barr, David ; Bartlett, Jennifer ; Baumeister, Willi ; Baumgarten, Bodo ; etc.
Duits
boek